2013
DOI: 10.1177/1457496913482249
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications after Cemented or Uncemented Hemiarthroplasty in Hip Fracture Patients

Abstract: Background and Aims: Both cemented and uncemented hemiarthroplasties are acceptable methods for treating displaced femoral neck fractures. Cemented hemiarthroplasty has traditionally been recommended as being more safe and reliable. However, the cementing process carries a risk of fat embolism and cardiovascular problems. This study attempted to determine whether these complications can be avoided when using a modern uncemented stem. Material and Methods:We retrospectively compared 222 hip fracture patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
3
32
2
Order By: Relevance
“…Previous papers comparing fracture rate are heterogenic. Some studies found a higher fracture rate in the uncemented group, ranging from 5.5 to 12% [3, 12, 13, 23] whereas others demonstrated no difference in fracture rate [4, 11, 22]. The fracture rate in the current study is higher than previous papers demonstrate.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous papers comparing fracture rate are heterogenic. Some studies found a higher fracture rate in the uncemented group, ranging from 5.5 to 12% [3, 12, 13, 23] whereas others demonstrated no difference in fracture rate [4, 11, 22]. The fracture rate in the current study is higher than previous papers demonstrate.…”
Section: Discussioncontrasting
confidence: 74%
“…Despite this, there have been reports that perioperative cardiovascular disturbances are more frequent in elderly patients with hip fracture when cemented stems are used rather than uncemented (Yli-Kyyny et al. 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Yli-Kyyny et al had a rate of 4.1% in 122 patients with cemented BHH. Fat embolism was the major cause of death during cementing [35]. Even though we used modern cementing techniques, including cement stopper, retrograde application, pressurisation and cement curing consequently over 14 minutes but this also resulted in collective death.…”
Section: Discussionmentioning
confidence: 99%